(untitled) (Research, Society and Development, 2021)
The present study analyzed the relationship between auditory perception and phonoarticulatory awareness of children with phonological disorders. Thus, he investigated why the child needs, in each age group, to acquire the correct phonemes; knew the relationship between auditory perception and the learned function of speech; understood how speech therapy resources can help in the auditory perception of the speech of children with phonological disorders. Integrative review was adopted as the method. All selected articles were carefully read and the contents found were standardized according to the proposed objectives. The results showed that phonological disorders in children may be related to failures in auditory perception, which, in turn, negatively influence the development of phonological awareness. It was found that there are several phonotherapy resources such as the NeuroAditive Stimulation System (SENA ©), the Auxiliary Software in the Rehabilitation of Auditory Disorders (SARDA, VoiceOnset Time (VOT) that can help in the auditory perception of the speech of children with phonological disorders.